The relationship between shoulder injuries and flexibility, shoulder range of motion characteristics in elite male Japanese water polo players - Segawa, E.; Komori, Y.; Hojo, T. (Japanese Journal of Physical Fitness and Sports Medicine, 2017)
The purpose of this study was to investigate relationship between the shoulder pain and the flexibility of the shoulder in Japanese elite male water polo players. We also conducted to find the physical characteristics of the range of shoulder rotation. Subjects were Japanese elite male water polo players that was 30 (study 1) and 40 (study 2). We measured and compared shoulder flexibility by finger vertebral distance (FVD). In study 2, a standard universal goniometer was utilized to measure range of shoulder rotation with the arm in 90 degrees of abduction. There is significant correlation range of motion on the dominant shoulder showed significant decrease in internal rotation and increase external rotation. The results indicate that decrease exists in the shoulder flexibility of elite water polo players with pain. Furthermore, our findings suggest that prevention or rehabilitation of painful water polo player`s dominant shoulder is considered to be existing two reasons that are at risk of developing shoulder pain because of the repetitive nature of swimming combined with throwing.